PJMHS 2022
DOI: 10.53350/pjmhs221611384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Job Stress on Job Performance among Speech-Language Pathologists in Pakistan

Abstract: Background: Job stress is now a widely used term use by speech-language pathologists. Workplace workload stress, high levels of time pressure, poor salaries, and the effect on mental health on job performance appear to be the main causes of low productivity in any work context. To combat stress, employees require a certain level of motivation as well as job stress management solutions. Objective: To find the effect of job stress and on Speech-Language Pathologists’ job performance in Pakistan. Methodology: It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…The results of the analysis obtained in this study indicate that the workload has a positive and significant effect on the performance of the Examiner at the Supreme Audit Agency of South Sumatra province, so the first hypothesis can be accepted. The results of this study are in line with the results of research from (van de Merwe et al, 2022;Tortia et al, 2022;Ijaz, 2022;Husin & Aisyah, 2021;Norawati et al, 2021;Marucci, 2021;Manurung, 2020;Azra, 2020;Balducci et al, 2021;Causse et al, 2019;Perlman, 2019;Dybvik, 2019;Polakitang et al, 2019;Nurwahhyuni, 2019) shows the results that the workload has a positive and significant effect on employee performance.…”
Section: Resultssupporting
confidence: 89%
“…The results of the analysis obtained in this study indicate that the workload has a positive and significant effect on the performance of the Examiner at the Supreme Audit Agency of South Sumatra province, so the first hypothesis can be accepted. The results of this study are in line with the results of research from (van de Merwe et al, 2022;Tortia et al, 2022;Ijaz, 2022;Husin & Aisyah, 2021;Norawati et al, 2021;Marucci, 2021;Manurung, 2020;Azra, 2020;Balducci et al, 2021;Causse et al, 2019;Perlman, 2019;Dybvik, 2019;Polakitang et al, 2019;Nurwahhyuni, 2019) shows the results that the workload has a positive and significant effect on employee performance.…”
Section: Resultssupporting
confidence: 89%
“…Spillover theory found that the influence aspect of work (Job Stress, Job Involvement, Job Satisfaction, & Job Motivation) is also determined by the CAKRAWALA -Repositori IMWI | Volume 6, Nomor 3, Juni 2023 p-ISSN: 2620-8490; e-ISSN: 2620-8814 surrounding environment which can produce both positive and negative things, therefore a balance is needed in the work and family environment (Hill et al, 2003) The dynamic relationship between workers and companies is where both provide mutual benefits or both provide positive ones to the other (Kamphorst & Swank, 2018). Organizational success depends on employee performance, however, high enthusiasm and competence among employees can trigger increased stress (Ijaz et al, 2022). High and frequent levels of work stress in the work environment greatly affect performance and can reduce employee engagement with their work (Akdemir et al, 2022).…”
Section: Introductionmentioning
confidence: 99%